Karakteristik Kimia, Fisik dan Organoleptik Cookies Tepung Mocaf Dengan Variasi Jenis dan Konsentrasi Lemak - margaretha ratna yasinta; catur budi handayani; afriyanti afriyanti (Universitas Veteran Bangun Nusantara, 2021)
Cookies are products that are oven-dried, made from wheat flour, sugar, fat and eggs. Cookies are not only made from wheat flour, there are many other local food ingredients that contain nutritional value and can be used as a basis for making cookies, one of which is mocaf flour. The purpose of this study was to determine the characteristics of mocaf cookies with various types fat in moisture content, swelling and organoleptic properties of mocaf flour cookies. The research method used a completely randomized design (CRD). The data obtained were analyzed statistically using Analysis Of Variance (ANOVA), if there is a significant difference between the test treatments, it is continued with the Duncan M Quotle Range Test (DMRT). Observation of chemical and physical properties includes testing of moisture content, swelling power. Organoleptic properties were observed with the parameters of taste, color and texture.Key words: cookies, fat, mocaf flour.